Differences and similarities in European railway disruption management practices. Issue 1 (June 2018) - Schipper, Danny; Gerrits, Lasse
Abstract: Disruptions severely undermine the reliability of railway systems. Consequently, a lot of investments are made to improve disruption management. Much has already been written about disruption management, often with the purpose of supporting operators in their decision making. However, to the best of our knowledge, this literature doesn't consider the structural differences of disruption management in different countries. An overview of the various ways in which disruptions are solved and conditions under which that happens could help rail infrastructure managers and train operating companies to reconsider the ways in which they operate. This paper takes stock of the similarities and differences in how disruptions are managed in Austria, Belgium, Denmark, Germany and the Netherlands. Of importance is not only how these systems work on paper, but above all what happens in practice, i.e. the habits and routines that operators have developed for solving disruptions. Highlights: Presents a comprehensive overview of rail disruption management in Austria, Belgium, Denmark, Germany, and the Netherlands. Takes stock of the similarities and differences in how rail systems have structured disruption management processes. Compares the countries on two important trade-offs: centralization vs. decentralization and anticipation vs. resilience.